Poplarism - Lansbury, Edgar (London : Independent Labour Party)
1924 1924 1920s 8 pages amenities of life. It is not sufficient to pay Sir Alfred Mond's weekly milk bill. We pay 41/- a week (plus rent and coal) for the maintenance of a man, woman and six or more children, and this is the limit of Poplar's scale. Is there anyone who will say that this is an extravagant sum? Will anyone say that such a family does not slowly starve on such a subsistence allowance? We are ashamed of our work. It is said that wages are lower than this figure. They are. But if people are starved on wages, must they starve to the same extent on relief? There may be an iron law of wages compelling employers to starve their workers ; there is no iron law to compel Guardians to starve the men, women and children under their care. According to Sir Alfred Mond, the maximum amount of relief for the largest family should he 10/- a week less than the wage of the lowest paid worker in ordinary employment. This figure to-day would be about 35/- a week. Sir Alfred would expect a whole family, whatever its size, to subsist on this figure, and to pay for rent, coal, gas, and boots, out of it. This is in accordance with Poor Law practice, and with the spirit of the 1834 Poor Law legislation. It means misery and starvation for hundreds of thousands of men, women and children. Liberals and Tories want to revive the practice and spirit of 1834. THE POPLAR ORDER. I will now deal briefly with the events that led to the issue of the notorious "Poplar Order." In the autumn of 1921, 32 members of the Poplar Borough Council were sent to prison. Technically their offence was Contempt of Court in refusing to levy certain rates on the people of Poplar to provide funds for the London County Council and other Central London authorities. In fact, their object in defying the Court was to force the Government to relieve the poorer Boroughs of London of the tremendous cost of maintaining the sick and unemployed destitute on outdoor relief and to place the burden on London as a whole. After six weeks of imprisonment their object was achieved. In November, following the release of the prisoners, an Act of Parliament was passed permitting Guardians to charge upon the Metropolitan Common Poor Fund the cost of outdoor relief. Under this Act, regulations were issued setting out a certain scale (called the Mond Scale) beyond which Guardians could not charge on the Central Fund. This scale was agreed upon beforehand by all the London Boards of Guardians, but was not binding upon them in the actual payment of relief. Many Boards paid more, some paid less. Those who paid more (Poplar included) had to pay the excess from their local rates. 5 15X/2/209/47